PENGARUH PENGETAHUAN LINGKUNGAN, PERSEPSI, DAN PERILAKU UMKM TERHADAP PENERAPAN EKONOMI HIJAU SYARIAH - Dewi fatimah; Herlina yustati; Anwar junaidi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to determine how the environmental knowledge, perceptions, and actions of MSME actors impact the implementation of Sharia green economy. This study employs an associative approach using a quantitative research design. The data used in this study are primary data. The data collection technique involved distributing questionnaires to respondents. The population of this study consists of 50 MSMEs. This study employed total sampling. The results of this study indicate that environmental knowledge and perceptions do not have a significant effect on the implementation of Sharia green economy practices among MSMEs in Sidodadi Village. Meanwhile, behavior has a positive and significant effect on the implementation of Sharia green economy practices among MSMEs in Sidodadi Village. However, environmental knowledge, perceptions, and behavior simultaneously have a significant effect on the implementation of Sharia green economy among MSMEs in Sidodadi Village. This is evidenced by the results of the F-test, which show a calculated F-value of 26.694 > the table F-value of 2.807, with a significance level of 0.000 < 0.05. In addition, the results of the coefficient of determination test showed an (R) Square value of 0.635, which means that the variables of environmental knowledge, perception, and behavior account for 63.5% of the variation in the adoption of Sharia green economy, while the remaining 36.5% is influenced by other variables outside the scope of this study.